Using Market Finance to Extend Water Supply Services in Peri-Urban and Rural Kenya - Advani, Rajesh (World Bank, Washington, DC, 2012)
This smart lesson explains how donor funds have been used to leverage domestic market finance and equity for investment in small piped water infrastructure in the peri-urban and rural areas of Kenya. Given the immense pressure on government and donor resources to achieve the Millennium Development Goals (MDGs), this approach shows that leveraging donor funds not only increases the volume of investments financed but improves the sustainability of these investments by linking debt service to system functionality.